AI Adoption, Work Pressure, and Psychological Resilience: Effects on Job Satisfaction and Employee Performance - Umban Adi Jaya; Indarta Priyana; Hasti Pramesti Kusnara; Bambang Somantri; Zeffanya Raphael Wijaya (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Digital transformation has encouraged organizations to adopt Artificial Intelligence (AI), which has important implications for employees’ working conditions and performance. This study aims to analyze the effects of AI adoption, work pressure, and psychological resilience on job satisfaction and its implications for employee performance in Bekasi, Indonesia. The study uses a quantitative approach with Structural Equation Modeling (SEM). Data were collected from 200 employees who are involved in AI-based organizational systems. The results show that AI adoption has a positive and significant effect on job satisfaction (β = 0.134; t = 1.856) and employee performance mediated through increased task efficiency and more accurate decision-making. In contrast, work pressure has a positive and significant effect on job satisfaction (β = 0.372; t = 4.614), indicating that excessive job demands can reduce job satisfaction and performance. Psychological resilience emerges as an important factor in maintaining emotional stability and employees’ ability to adapt to stress, which positively affects job satisfaction. Furthermore, job satisfaction has a direct effect on employee performance, showing that more satisfied employees tend to perform better. This study concludes that successful AI integration requires a balance between technological innovation and employee well-being, supported by resilient development programs and supportive organizational policies.